(untitled) (Ágora UNLaR, 2019)
Podemos entender el fenómeno de la literatura latina de los Estados Unidos como una expresión literaria de una identidad cultural surgida de los procesos migratorios de nuestro tiempo. En este trabajo me propongo estudiar dos novelas de escritoras migrantes de identidad escindida, por un lado, Under the Feet of Jesus (1996) de la mexicano-americana Helena María Viramontes y por otro Dreaming in Cuban (1992) de la cubano- americana Cristina García. Es mi intención indagar la manera en que dos protagonistas femeninas, Estrella y Pilar respectivamente, configuran el ideal del sueño americano en un contexto rural como San Joaquín Valley, California y en un contexto urbano como el barrio de Brooklyn, New York. Ambas novelas fueron escritas durante la década de los noventa y sitúan su narración en la década de los sesenta. URBAN AND RURAL ELEMENTS IN THE CONFIGURATION OF THE AMERICAN DREAM: UNDER THE FEET OF JESUS AND DREAMING IN CUBAN Abstract The phenomenon of Latino literature in the United States can be understood as a literary manifestation of cultural identity which emerges as part of processes of migration. This work explores two novels by migrant women writers of hyphenated identity: Under the Feet of Jesus (1996) by the Mexican-American Helena María Viramontes and Dreaming in Cuban (1992) by the Cuban- American Cristina García. This work explores the way in which two female protagonists, Estrella and Pilar, configure the ideal of the American dream from the rural context of San Joaquin Valley, California, and the urban context of the neighbourhood of Brooklyn, New York. Both novels were written during the 1990s and they are set in the 1960s. Key words: identity; migration; American dream; urban context; rural context